Feminizacja prekariatu. Polska na tle innych krajów Europy - Polkowska, Dominika (Annales. Etyka w Życiu Gospodarczym, 2016)
Precarity applies to people who, in order to survive, need to work in a low-quality job, which is uncertain, temporary, low-paid, with no prospect of promotion, no security and no contract. In this sense, the precariat is a category related mostly to the secondary segment of the labour market, according to the concept of a dual labour market. It is also the universal feature of Post-Fordism and the modern working conditions in which women, more often than men, are located in the ‘worst’segment of the labour market. In this context, it can be noted that since the beginning of the era of globalization, women start working particularly in those sectors that were more uncertain and unstable e.g. in services and trade. It was feminization in a double sense: there were more and more working women on the one hand, and on the other hand, the flexible jobs were undertaken usually by women. Most of these kind of jobs were precarity jobs. Precarity is combined with insecurity, which does not allow the people in this group to plan anything, and wages so low that they can’t afford a decent life. In the article I would like to prove that the threat of precariat is more probable for women than men. I present data related to precarity for Poland compared to other European countries (based on data from Eurostat and the OECD).